After the collapse of communism comparative lessons of transition - McFaul, Michael 1963-; Stoner, Kathryn 1965- (Cambridge University Press, 2004)
This collection of essays is the result of a conference convened at Princeton University marking the ten-year anniversary of the collapse of the Soviet Union. Some of the best minds in post-Soviet studies focused on the task of identifying in what ways the post-Communist experience with transition has confirmed or confounded conventional theories of political and economic development. The result is a rich array of essays examining vital aspects of the transitional decade following the Soviet collapse and the comparative lessons learned. These essays explicitly tally the gains and losses to post-Soviet countries of the last ten years as well as comparing the post-Soviet experience implicitly and explicitly with that of other developing countries. Each essay blends political science theory with fresh empirical analysis
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Politik; Post-communism / Europe, Eastern / Congresses; Post-communism / Former Soviet republics / Congresses; Post-communism / Russia (Federation) / Congresses; Democracy / Europe, Eastern / Congresses; Democracy / Former Soviet republics / Congresses; Democracy / Russia (Federation) / Congresses; Wirtschaftsentwicklung; Postkommunismus; Politischer Wandel; Demokratisierung; Nationalstaat; Europe, Eastern / Politics and government / 1989- / Congresses; Former Soviet republics / Politics and government / Congresses; Russia (Federation) / Politics and government / 1991- / Congresses; Russland; Osteuropa; Konferenzschrift